Hubungan Kecemasan Kejadian COVID-19 dengan Kualitas Hidup Lansia di Kecamatan Ende Tengah Kabupaten Ende, Provinsi Nusa Tenggara Timur - Syaputra Artama; Khrispina Owa (Jurnal Kesehatan Komunitas, 2022)
The increase in COVID-19 cases in the elderly presents many challenges in the field of health services during the current pandemic The high number of cases has a bad impact on mental health in the elderly. Anxiety is a first-order mental health problem in the elderly. Efforts to deal with anxiety experienced during this pandemic have a very positive effect on improving health and providing a better quality of life. This study aims to determine the relationship between the anxiety of covid-19 events and the quality of life of the elderly. The research method used a descriptive cross-sectional study design with a total sample of 100 respondents with sampling carried out a consecutive sampling from February 2022 to May 2022. Bivariate data analysis using spearman test. The results showed that the relationship between respondents' anxiety about the incidence of COVID-19 and quality of life obtained a p-value = 0.019 meaning that there was a significant relationship between respondents' anxiety and quality of life. The result of a correlation value of -0.234 has a weak relationship strength with a negative correlation which means that the fewer anxiety respondents have about the incidence of COVID-19, the better their quality of life and vice versa. It can be concluded that the importance of the role in providing physical, emotional, and psychological support to the elderly as well as recommendations for physical activity so that in the end it can have a positive effect on changes in their quality of life.